Advances in Multimedia Information Processing - PCM 2010 11th Pacific Rim Conference on Multimedia, Shanghai, China, September 2010, Proceedings, Part II - Qiu, Guoping; Lam, Kin Man.; Kiya, Hitoshi; Xue, Xiang-Yang.; Kuo, C.-C. Jay.; Lew, Michael S.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 11th Pacific Rim Conference on Advances in Multimedia Information Processing, held in Shanghai in September 2010.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Multimedia systems; Electronic books